How Preceptor Behaviour Shapes the Future of Medical Professionals - Alshareef MH; Flemban AF (Advances in Medical Education and Practice)
Maram H Alshareef,1 Arwa F Flemban2 1Department of Community Medicine and Pilgrims Health, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 2Department of Pathology, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi ArabiaCorrespondence: Maram H Alshareef, Department of Community Medicine and Pilgrims Health, Faculty of Medicine, Umm Al-Qura University, Makkah, 21955, Saudi Arabia, Email mhashareef@uqu.edu.saAbstract: Preceptors play an indispensable role in shaping the future of healthcare. They bridge theoretical learning and practical clinical expertise in a rapidly evolving medical education landscape. Their influence extends beyond knowledge transfer, embodying the values, attitudes, and professionalism essential to competent medical practice. Bandura’s Social Learning Theory posits that individuals learn through observation and modelling. Applying this theory supports the assumption that trainees acquire skills and professional norms by observing preceptor behaviour, a process known as vicarious learning. They transmit clinical competencies, ethical standards, and interpersonal skills critical for patient-centred care. Despite their significance, challenges such as increasing workloads, diverse trainee needs, and the complexities of modern healthcare often impede their ability to mentor effectively. Preceptors shape trainees’ professional identities and ethical standards, which are significantly influenced by the hidden curriculum, the set of unspoken or implicit lessons conveyed outside the formal curriculum. Globally, there is growing recognition of the need to support and enhance the role of preceptors in medical education. Due to several challenges, some factors might prevent preceptors from maintaining their role model status, including the need for experience, continuous learning, and adaptation to diverse trainee needs. Strategies such as engaging in reflective practices and implementing effective stress management techniques are crucial for preceptors to navigate these barriers and uphold their status. However, few studies have synthesised the various dimensions of preceptor influence, including role modelling, communication skills, and the hidden curriculum. This review aims to fill this gap by exploring the variable role of preceptors in shaping medical trainees’ professional development. It highlights the theoretical underpinnings of preceptorship, discusses the challenges preceptors face, and proposes evidence-based strategies to enhance their impact on future healthcare professionals.Keywords: trainee, role model, communication, hidden curriculum